ESCAPE‐Allergy: Evaluating screening for children and adolescents with penicillin allergy. (29th July 2021) - Rischin, Kobi J; Mostaghim, Mona; Rao, Arjun; Smith, Bridget; O'Brien, Tracey A; Trubiano, Jason A; Frith, Katie; McMullan, Brendan
Abstract : Aim: Penicillin allergy labels are frequently encountered in children and are associated with significant harms. Most children are falsely labelled and can safely tolerate a penicillin but delabelling strategies are underutilised and paediatric‐specific resources are lacking. The aim of this study was to evaluate an allergy assessment tool for children in hospital. Methods: We evaluated a paediatric‐adapted penicillin allergy assessment tool, using an online survey of clinicians in a tertiary paediatric hospital, with 10 hypothetical potential penicillin allergy or adverse reaction cases (including non‐allergy reactions). For each case, respondents were asked to use the tool to assign a reaction phenotype and recommend management. We determined the tool's sensitivity, specificity and acceptability to end users. Results: We evaluated 30 complete survey responses from senior and junior medical staff, nurses and pharmacists. The tool's overall sensitivity was 80.7% (95% confidence interval (CI) 74.2–87.1%) for assigning the correct reaction phenotype and 85.3% (95% CI 79.4–91.3%) for appropriate management. The tool had high sensitivity for identifying immediate hypersensitivity reactions at 95.6% (95% CI 90.2–100%). Most respondents agreed or strongly agreed that they would use the tool in their practice (22/30, 73.3%). Conclusion: This survey evaluated a paediatric‐adapted penicillin allergy assessment tool in a tertiary paediatric hospital among multidisciplinary clinician groups. The tool performed well overall and had high safety in identifying immediate hypersensitivity reactions. Further research to support implementation of allergy assessment and delabelling programmes among children is required.